A different mirror - Schneider, Richard P., author; Lear, Kevin L., author; Gourley, Paul L., author; IEEE, publisher (Colorado State University. Libraries, 1994)
Mirrors grown in the crystalline structure ease manufacture of vertical-cavity lasers, which emit collimated circular beams and can form large two-dimensional arrays. The authors discuss the fabrication of the surface emitting laser mirrors. By means of techniques such as molecular beam epitaxy and metal-organic vapor phase epitaxy, hundreds of layers of semiconductor materials can be grown one on top of the other. By mixing and matching the materials to create "designer" alloys, it is possible to grow a crystalline structure with all the electrical and optical properties desired for its various parts. This method of tailoring semiconductor structures is called bandgap engineering. The principles of the mirrors and their applications are discussed.
Keywords: optical workshop techniques; molecular beam epitaxial growth; mirrors; laser accessories; semiconductor growth; semiconductor laser arrays